2006
DOI: 10.1007/s00381-006-0200-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of quality of life and clinical status of children operated on for intractable epilepsy

Abstract: Surgical treatment of intractable epilepsy is an effective method in terms of both seizure control and QOL improvement. Our results indicate the improvement in QOL of all operated patients. The improvement in QOL was accompanied by decrease in frequency and 'positive' changes in morphology of seizures. Improvement in QOL, as equivalent to seizure reduction rate, may influence further differentiation of qualification methods and surgical procedures of epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 15 publications
2
16
0
Order By: Relevance
“…With respect to the overall outcome of QOL, the survey found that almost all patients showed significant improvement, which concurs with other results 3,14,[16][17][18][22][23][24][25][26][27] . Despite the excellent control of seizures, only one of our patients had a decrease in the overall QOL score (subject 13), mainly due to social, school and behavioral factors.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…With respect to the overall outcome of QOL, the survey found that almost all patients showed significant improvement, which concurs with other results 3,14,[16][17][18][22][23][24][25][26][27] . Despite the excellent control of seizures, only one of our patients had a decrease in the overall QOL score (subject 13), mainly due to social, school and behavioral factors.…”
Section: Discussionsupporting
confidence: 88%
“…All subjects indicated a high level of perception of seizure control (attributed to a maximum value when questioned about it). Other studies have also found a high degree of seizure control 14,16,19,26 and positive correlations between the control and the degree of patient satisfaction 14,16,17,[23][24][25][26][27][28] . However, our findings were higher than those of the literature and, again, this is probably due to the strict inclusion criteria in our study and the fact that we have focused on surgery for TLE only, excluding other more serious etiologies.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Other investigators have described a similar relationship between epilepsy duration and seizure outcomes, 41,58 sug gesting that earlier operative therapy may improve the likelihood of Engel Class I outcome. Furthermore, sev eral studies have shown that pediatric patients who at tain seizure control postoperatively may also benefit from improved intellectual and cognitive ability, 42,53 better memory function, 40 decreased medication use and side effects, 32,46 fewer behavioral problems, 45 and overall im proved quality of life 38,40 compared with patients with continued seizures. Patient and family surveys have also suggested higher levels of education, employment status, independence, and overall satisfaction associated with Engel Class I outcome compared with other Engel class outcomes.…”
Section: Discussionmentioning
confidence: 99%